الطفل الجزائري والتعليم الرقمي عبر اليوتيوب في ظل جائحة كورونا: قراءة في التحديات - خديجة, بن دنيا; فطيمة, شرشار (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى البحث في موضوع الطفل الجزائري والتعليم الرقمي من خلال موقع اليوتيوب في ظل انتشار فيروس كورونا، الذي فرض الحجر الصحي للتعايش الآمن مع الفيروس، لأهمية التعليم الرقمي في هذا الظرف الحتمي، حيث أصبح ضرورة تكنولوجية لضمان استمرارية التعليم. إلا أن تطبيق التعليم الرقمي في الجزائر، وإتاحة القنوات التعليمية عبر اليوتيوب في ظل هذه الظروف الاستثنائية، ودفع الطفل لمتابعة الدروس بهذه الطريقة، تواجهه عديد التحديات، وهو ما سنتناوله من خلال هذه الدراسة. Abstract: This study aims to research the topic of the Algerian child and digital education through YouTube in the light of the spread of the Corona virus, which imposed a quarantine for safe coexistence with the virus, because of the importance of digital education in this inevitable circumstance, as it has become a technological necessity to ensure the continuity of education. However, applying digital education in Algeria, and making educational channels available via YouTube during these exceptional circumstances, in addition to pushing the child to follow lessons in this way, faces many challenges, which we will discuss through this study.
مقال
Keywords: التعليم الرقمي؛ اليوتيوب؛ التحديات؛ جائحة كورونا؛ الطفل الجزائري.; Digital education; Youtube; challenges; Corona cataclysm; Algerian child